Produção biotecnológica de etanol a partir das frações celulósica e hemicelulósica do bagaço de sorgo sacarino - Camargo, Danielle (2016)
Ethanol is considered a promising alternative to fossil fuels and causes less environmental impact, which implies an increase in the consumption of biofuel. To meet this demand, research has been conducted with alternative raw materials to complement the production of first generation ethanol. In Brazil, sweet sorghum is being studied for the expansion of sugarcane industry due to its rapid growth and the possibility of cultivating it during the season-cropping of sugarcane. However, during processing of sweet sorghum for ethanol production, generation of bagasse occurs, a material composed primarily of cellulose and hemicellulose, which can be considered a potential source of feedstock for bioprocesses. Therefore, the purpose of this study was the use of the sugars from the hemicellulose and the cellulosic fractions of the sweet sorghum bagasse, for the production of second generation ethanol by pentoses and hexoses fermentation yeasts, respectively. After chemical characterization of sorghum bagasse of six cultivars, they were subjected to mild acid hydrolysis with variations in temperature (111; 115 °C and 121), time (40, 50, and 60 min) and concentration of sulfuric acid (075; 1.25 and 1.75% w/v) using a central composite design (DCC) and response surface to find the condition that is conducive to high concentrations of sugars and less toxic compounds in the hemicellulosic hydrolysate. After the hydrolysate was concentrated and detoxified, it was submitted to fermentation by the yeast Schefferosomyces stipitis in a bioreactor at 30 °C, with kLa 4.9 h-1, pH 5.5 and volume of 4.5 liters. The solid biomass (cellulignin) that resulted from the acid treatment was submitted to evaluation of the percentage of cellulose, hemicellulose and lignin and then to studies with variation in the concentration of NaOH (1; 2.5 to 4%) and time (20, 40 and 60 min). After the treatment with the best condition of removal of lignin, cellulosic biomass was subjected to enzymatic hydrolysis with variation in the concentration of cellulase NS22086 (15, 20 and 25 FPU/g) and β-glucosidase NS22118 (1/3 to 2/3) and temperature of 38; 41 to 44 °C, in order to obtain the best saccharification rates and high glucose concentrations. The production of ethanol from the cellulosic fraction was then carried out with Kluyveromyces marxianus, during simultaneous saccharification and fermentation (SSF) at three different temperatures (38, 41 and 44 °C) for fermentation. The chemical composition between different varieties studied was similar and varied from 22-26% of lignin, from 30-32% of hemicellulose and 32-37% of cellulose. In the study of the hydrolysis conditions of hemicellulose, it was found that the acid concentration was the most important factor, and the condition that resulted in the highest concentration of sugars (14.22 g/L xylose and 2.42 g/L glucose) was 1.75% H2SO4, 40 minutes and 121 °C. This same condition showed low quantities of toxic compounds (1.34 g/L of acetic acid, 0.90 g/L of phenol; 124.54 mg/L of hydroxymethylfurfural and 978 mg/L furfural). The production of ethanol by S. stiptis in the hemicellulosic hydrolysate resulted in a concentration of 22 g/L ethanol, Yp/s of 0.40 g/g; Yx/s 0.28 g/g and Qp of 0.34 g/L.h-1. For the study of cellulignin delignification it was found that 2.5% NaOH for 60 minutes was the best condition for the removal of lignin (68%). During the enzymatic hydrolysis of the cellulosic portion, it was verified that the increase of cellulase from15 to 25 FPU/g resulted in higher concentration of glucose. In addition, the increase of β-glucosidase also resulted in the largest amount of glucose in a shorter time. The temperature also increased and accelerated the process of saccharification of cellulose. The simultaneous saccharification fermentation with K. marxianus was shown to be affected by the temperature studied, and the maximum ethanol concentration was reached (9.41 g/L) after 72 hours at 41 °C. With these results, it was possible to consider that the bagasse of sweet sorghum is a promising material in the field of second generation ethanol production both from hemicellulose and cellulose.